Communication Within and Among Faith-Based Organizationsin Community Empowerment Program - Hadiyanto A. Rachim; Nunung Nurwati; Gigin G. K. Basar (Universitas Muhammadiyah Ponorogo, 2019)
The issue of this research is concerning the communication within and among Zakat Management Organizations (OPZs) as Faith-Based Organization (FBO). The main research problem is how OPZ(s) can successfullydevelop cooperationin increasing both public trust and institutional productivity. Interpretive Approach through Social Construction Theory was used as a reference to see the process of organizational communication through OPZ’s communicator ethos. The research method used was qualitative with a technique of case study, and informants were from OPZ’s West Java unit. The results showed that the communicator ethos as a source of credibility in communicationwithin and among OPZs, derived from Islamic Teachings, applicable (positive)laws, and basic guidelines of OPZs, can produce organizational values as the basis of implementing cooperation in community empowerment programs. Cooperation among OPZsin an empowerment program is more related to personal power and interpersonal power aspectsthan to political power aspect. There is a need to strengthen openness and mutual trust values among the OPZs, changes in zakat regulation, more transparent, accountable and equitable governance in order to increase trust, realization of zakat potentials, and prosperity.